The genomic prehistory of peoples speaking Khoisan languages. (19th October 2020) - Pakendorf, Brigitte; Stoneking, Mark
Abstract: Peoples speaking so-called Khoisan languages—that is, indigenous languages of southern Africa that do not belong to the Bantu family—are culturally and linguistically diverse. They comprise herders, hunter-gatherers as well as groups of mixed modes of subsistence, and their languages are classified into three distinct language families. This cultural and linguistic variation is mirrored by extensive genetic diversity. We here review the recent genomics literature and discuss the genetic evidence for a formerly wider geographic spread of peoples with Khoisan-related ancestry, for the deep divergence among populations speaking Khoisan languages overlaid by more recent gene flow among these groups and for the impact of admixture with immigrant food-producers in their prehistory.